Subjective Excess: Aesthetics, Character, and Non-Normative Perspectives in Serial Television After 2000 - (:unkn) unknown (My University, 2023)
This dissertation aims to fill gaps in contemporary television scholarship with regards to aesthetics and character subjectivity. By analyzing eight series that have all aired after 2000, there is a marked trend in series that use an excessive visual and aural style to not only differentiate themselves from other programming, but also to explore non-normative perspectives. Now more willing to explore previously taboo topics such as mental health, addiction, illness, and trauma, the shows featured in this dissertation show how a seemingly excessive televisual aesthetic works with television’s seriality to create narrative complexity and generate character development. Chapters are arranged by mode of production with the first chapter focusing on the series Grey’s Anatomy and Hannibal as a means of exploring the production and distribution practices surrounding network TV. The second chapter examines the basic cable series Crazy Ex-Girlfriend and Legion and posits how the narrowcasting of cable allows for more nuanced character representations through aesthetics. In the third chapter, the impact HBO has had on the television medium is explored through Carnivàle and Euphoria. The final chapter looks at contemporary series The Boys and Unbreakable Kimmy Schmidt as a way to better understand how the medium’s production and distribution has shifted during the convergence era. Ultimately, this dissertation will argue that in addition to further explorations of aesthetics, television studies is in need of a medium specific vernacular for creating meaningful textual analyses that avoid an overreliance on cinematic terminology.
Keywords: Character; Cinematic; Narrative; Seriality; Television; Televisuality